Church polity and politics in the British Atlantic world, c.1635-66 - Vernon, Elliot, 1972-; Powell, Hunter (Politics, culture, and society in early modern Britain., 2020)
This volume explores church polity and its relationship to politics in the British Atlantic world during the mid-seventeenth century. It addresses the conflicts between church and state, the ecclesial factions of episcopalianism, presbyterianism and congregationalism and the effects of these conflicts at the level of nations and localities.